A one step real-time RT-PCR assay for the quantitation of Wheat yellow mosaic virus (WYMV) - Liu, Wenwen (BioMed Central, 2013)
BACKGROUND: Wheat yellow mosaic virus (WYMV) is an important pathogen in China and other countries. It is the member of the genus Bymovirus and transmitted primarily by Polymyxa graminis. The incidence of wheat infections in endemic areas has risen in recent years. Prompt and dependable identification of WYMV is a critical component of response to suspect cases. METHODS: In this study, a one step real-time RT-PCR, followed by standard curve analysis for the detection and identification of WYMV, was developed. Two reference genes, 18s RNA and β-actin were selected in order to adjust the veracity of the real-time RT-PCR assay. RESULTS: We developed a one-step Taqman-based real-time quantitative RT-PCR (RT-qPCR) assay targeting the conserved region of the 879 bp long full-length WYMV coat protein gene. The accuracy of normalized data was analyzed along with appropriate internal control genes: β-actin and 18s rRNA which were included in detecting of WYMV-infected wheat leaf tissues. The detectable end point sensitivity in RT-qPCR assay was reaching the minimum limit of the quantitative assay and the measurable copy numbers were about 30 at10(6)-fold dilution of total RNA. This value was close to 10(4)-fold more sensitive than that of indirect enzyme-linked immunosorbent assay. More positive samples were detected by RT-qPCR assay than gel-based RT-PCR when detecting the suspected samples collected from 8 regions of China. Based on presented results, RT-qPCR will provide a valuable method for the quantitative detection of WYMV. CONCLUSIONS: The Taqman-based RT-qPCR assay is a faster, simpler, more sensitive and less expensive procedure for detection and quantification of WYMV than other currently used methods.